OPTIMALISASI PERKEMBANGAN BAHASA ANAK MELALUI TELEVISI : SUATU KAJIAN LITERATUR PSIKOLINGUISTIK - Syarifah Lubna (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
Language has an important role to help people communicate and survive their life. It also differentiates human than other creature. That is one of the reasons why people learn to talk as humans. There are six stages of language development. Many factors also take part in this language development of human being, including television. Television has influenced the way of people think and talk. For Indonesian children who watch television in more hours than they read books, television has more power to impact and affect not only their behavior, manner and thought but also their language. To bring all effect of this television runs in a good way, teachers, parents and also the society and government need to help each other to support and implement situational and conditioning that help children aware and take good advantages of television for their language development.